1991
DOI: 10.1111/j.1365-2621.1991.tb07961.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation Kinetics of Food‐borne Yeasts

Abstract: The thermal inactivation kinetics of three food-borne yeasts from heattreated products-two Sacc. cerevisiae and one Zygosacc. roux&have been determined. Thermal treatment and evaluation of results were carried out according to the dynamic heat destruction method. Results for 0.5% (whv) glucose as heating medium expressed in Ds5 values were 1.05, 2.67 and 0.16 min, respectively. The respective z values were 4.00, 6.23 and 5.55"C. The apparent activation energy for heat destruction calculated from the Arrhenius … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 51 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…Our ongoing research showed that these isolates could be completely inactivated by heating at 80°C for 15 s in apple juice concentrate (unpublished work). Previous studies also reported that D values of yeast rarely exceed 1 min at 55°C in juice products (Török and King 1991;Splittstoesser 1996). Therefore, there is evidence to support our hypothesis that these isolates probably cannot contaminate the apple juice concentrate because of the processes of the production line.…”
Section: Speciessupporting
confidence: 86%
“…Our ongoing research showed that these isolates could be completely inactivated by heating at 80°C for 15 s in apple juice concentrate (unpublished work). Previous studies also reported that D values of yeast rarely exceed 1 min at 55°C in juice products (Török and King 1991;Splittstoesser 1996). Therefore, there is evidence to support our hypothesis that these isolates probably cannot contaminate the apple juice concentrate because of the processes of the production line.…”
Section: Speciessupporting
confidence: 86%
“…These results may be explained by the evident thermal effect, such that for the alternative arrangement (i.e., first the MW treatment and then the UVC), the inactivation turned out to be higher within the continuous process (MW-UVC) than that in the staged one (MW s -UVC s ) for both tested velocities. 3.4.1 | S. cerevisiae inactivation Török and King (1991) tively. In another study where the UV light was combined with mild temperatures, Gouma et al (2015) reported that UVC and heat (57-60 C) treatments caused 5-log reductions in S. cerevisiae in the apple juice.…”
Section: Uvc S -Mw S and Mw S -Uvc S Combined Treatments By Stagesmentioning
confidence: 99%
“…In the food industry, the control of the spoilage and pathogenic microorganisms was traditionally carried out by means of using thermal processes, to ensure the partial or total elimination of the microflora present [17,18]. Together with an aseptic and hermetic packaging, it was possible to effectively extend the shelf life of the food products ensuring at the same time its microbiological safety [19,20].…”
Section: Technologies For Spoilage Yeast Control 21 Early Technologiesmentioning
confidence: 99%